OPTIMALISASI PENGELOLAAN ARSIP DAN HAMBATAN IMPLEMENTASINYA DALAM MENYEMPURNAKAN KUALITAS PELAYANAN DI KANTOR REGIONAL X BKN DENPASAR - Ida Bagus Ngurah Wimpascima; Gusti Ayu Mahanavami; Debilia Kedu Wela; Ni Nyoman Menuh (Juremi: Jurnal Riset Ekonomi, 2024)
Archive, as a collection of records and recordings of activities, plays a vital role in the smooth operation of an institution. This research aims to optimize archive management and identify implementation barriers at the Regional Office X of the National Civil Service Agency (BKN) in Denpasar, with a focus on improving service quality. The research method used is qualitative with a descriptive approach. Data were obtained from Administrative Staff through interviews and documentation. Data analysis involved data reduction, data presentation, and drawing conclusions. The results show that archive management includes creation, storage, retrieval, and disposal of archives. Identified constraints include lack of human resources and inadequate facilities. The archive creation process follows predetermined formats, and archival management uses alphabetical and sequential numbering systems. Archive retrieval is still manual with computer assistance, and archive disposal is done through burning for archives that no longer have value. With the aim of improving service quality, this research suggests establishing a consistent timeframe for the archive disposal process, adding facilities, space, and filing cabinets, as well as increasing human resources, especially archivists. These steps are expected to optimize archive storage activities at the Regional Office X of BKN in Denpasar and support better service efficiency